EPIDEMIOLOGY, RISK FACTORS AND DIAGNOSIS OF CHRONIC RENAL FAILURE - M.K. GULOV; KH.K. RAFIEV; S.M. ABDULLOEV (Avicenna Tajik State Medical University, 2018)
Objective: Analysis of the literature shows that the number of patients with chronic renal failure (CRF) increases every year. To date known more than twenty renal diseases, the end of clinical manifestation of which is CRF. Studies of recent years show that in CRF genesis and progression leading role plays arterial hypertension, smoking, age, male sex, dyslipidemia, diabetes mellitus, some autoimmune diseases, metabolic disorders of calcium and phosphorus, the use of nephrotoxic drugs, the effects of psycho-emotional and oxidative stress, malfunction of the renin-angiotensin-aldosterone system, etc. At the present stage, for diagnosis of violations of the glomerular filtration rate, ordered ten, most important of them - Cystatin C method. Another non-invasive method is doppler ultrasound. In spite of this, the issues of early diagnosis of chronic kidney disease remain to the end not studied and not solved, which requires the development of new working algorithms.